REFORMASI HUKUM TATA NEGARA MELALUI AMANDEMEN KONSTITUSI (KRITIK TERHADAP PELAKSANAAN OTONOMI DAERAH PASCA REFORMASI) - Indra Fatwa (JOURNAL EQUITABLE, 2021)
The purpose of this study was to find out the problems of the practice of regional autonomy in post-Reformation Indonesia. The research method used is a normative legal method with a descriptive analysis approach. The results of the study show that the practice of regional autonomy in post-Reformation Indonesia is still constrained in its implementation. This can be seen from the various laws and regulations derived from the 1945 Constitution of the Republic of Indonesia which still put forward a centralistic spirit. The conclusion of this research is that it is necessary to reform the law from derivative products of the constitution which regulates the implementation of regional autonomy. This can be started by making amendments to the Constitution. Keywords: Regional Autonomy, Amendments, Constitution.